Experimental and Computaional Study of Compartmented Fluidized Bed Gasifier (CFBG) - Wee, Siaw; Chok, Vui; Gorin, Alexander; Chua, Han (-, 2008)
A pilot scale (0.5 tones/day) air-blown compartmented fluidized bed gasifier (CFBG) consisting of two compartments, the combustor and the gasifier, operating at bubbling fluidized mode has been constructed for medium calorific value syngas (>11 MJ/Nm3) production from biomass. The hydrodynamics of CFBG is studied experimentally and computationally. The experiments are carried out in a custom-made transparent CFBG cold model. The computational fluid dynamics (CFD) software, FLUENT, is employed in modeling the fluidized bed containing monodispersed size Geldart B particles, river sand, of 272 ?m and 2620 kg/m3 in diameter and density respectively. A three-dimensional Eulerian-eulerian granular model with closure laws according to the kinetic theory of granular flow is chosen to simulate the multiphase environs at 0.2 ? 3.2 Umf.The CFD simulated results show reasonably well agreement with experimental results in terms of bed pressure drop, bed expansion ratio and minimum fluidization velocity. The experimentally determined average fluidization quality over the operating bed height range is approximately 0.8.